Knowledge and Awareness of Risk Factors for HIV Infection and about HIV Testing among Medical Students in Warsaw - Justyna Kowalska; Martyna Cholewik; Carlo Bieńkowski; Aleksandra Maciejczyk; Dominik Bursa; Agata Skrzat-Klapaczyńska (Viruses, 2024)
Background: The number of late diagnoses of HIV remains very high in Poland, leading to a high proportion of patients developing and dying of HIV-related diseases. The main reason for this is the very low utilization of HIV testing. Our analyses aimed to investigate knowledge about the indications for HIV testing among medical university students, as well as identify their own HIV testing experiences. Material and methods: A cross-sectional survey study was designed to collect information on the students’ demographics and their experiences of HIV testing, as well as their knowledge of virus transmission and the indications for testing. Data were collected as part of the HIV_week@WUM project conducted at the Medical University of Warsaw in parallel with the 18th European AIDS Conference, which took place in Warsaw between 18 and 21 October 2023. Results: In total, 545 questionnaires were collected. The median age of the study participants was 20 (interquartile range (IQR): 19–22 years). The majority of respondents were as follows: women (67.5%), born in Poland (97.8%), and were attending the medical faculty (56.7%). Only 114 (21.43%) participants had ever been tested for HIV. For all modes of HIV transmission, most of the respondents overestimated the risk of acquiring HIV, but, at the same time, they had never been tested for HIV. Conclusions: Only one in five health sciences students has ever had a test for HIV, which is less than estimates for the general population of Warsaw. There is an ongoing need to popularize testing among future health care providers in order to address both the indications for testing for individuals and the better use of HIV testing in clinical practice.